Efektivitas Aplikasi M-Paspor Dalam Pelayanan Publik - Putri Dia Sari; Redia Annisa Al Karimah; Sarah Salsabilla (Jurnal Media Administrasi, 2024)
The utilization of technology in public services promises effectiveness and efficiency to help all lines of human work because it can speed up the work process. all lines of human work because it can speed up the work process carried out. The realization of egovernment can be realized as one form of technology utilization in the public service sector. The M-Passport application is one of the implementations of e-government in the field of immigration. The implementation of the M-passport application will be reviewed for effectiveness whether it can realize the effectiveness of e-government services. effectiveness in e-government services to the community. This can be seen from the implementation of the application passport application that is getting easier and faster with the help of technology and technology and systems that exist in the M-Passport Application. This also supports the implementation of egovernment-based public services and helps oversee social distancing policies during the Covid-19 pandemic in Indonesia so that we can continue to provide optimal immigration services